Pengaruh Temperatur Pengeringan Terhadap Swelling dan Tensile Strength Edible Film Hasil Pemanfaatan Tepung Umbi Porang (Amorphophallus muelleri Blume) - Amyranti, Mutia; Nurlatifah, Ismi; Maftukhah, Siti; Arlianti, Lily (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
Food packaging is the process of protecting a food product to maintain durability and quality consistency. Edible film made from porang tubers is a sustainable and innovative solution to reduce plastic waste and improve food preservation. Porang tuber (Amorphopallus muelleri blume) is a valuable plant as its high glucomannan content can be processed into porang flour. The drying process is one of the important steps in the preparation of porang tuber flour. One of the polysaccharides used in edible films is starch from glucomannan derived from Porang tubers. Glucomannan is an alternative material developed because of the high polysaccharide content in porang tubers, namely mannan, which has the ability to form a good film layer, good biocompatibility, biodegradable and has the ability to form a gel. This study was conducted with the aim to determine the effect of drying temperature on the results of edible films obtained, in terms of swelling and tensile strength values using porang tuber starch. The main stages of this research are the preparation of glycerol-plastized porang tuber flour solution and then the stage of making porang tuber flour edible film. In the manufacture of edible film, the drying process is carried out with temperature variations of 40, 50 and 600C. The highest swelling and tensile strength values were obtained in porang flour edible film at 50 0C, where the swelling and tensile strength values were 61.1% and 0.75 MPa.